Zrcalna simetrija in Laurentovi polinomi - Filip, Matej (Obzornik za matematiko in fiziko, 2024)
Mirror symmetry originally describes the connection between two geometric objects called Calabi-Yau manifolds. If two Calabi-Yau manifolds are mirror symmetric they are geometrically distinct yet equivalent when viewed from the physical side of string theory. Mirror symmetry has many mathematical formulations and generalisations that go beyond the Calabi-Yau manifolds. In this paper we will present one aspect of mirror symmetry that can be formulated in terms of elementary convex geometry.
Keywords: Calabi-Yau manifolds; Calabi-Yau mnogoterosti; Laurent polynomials; Laurentovi polinomi; mirror symmetry; zrcalna simetrija